2014
DOI: 10.5012/bkcs.2014.35.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Thermoresponsive Copolymers with Tunable LCST and UCST in Water

Abstract: A thermoresponsive polymer, poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA), was successfully synthesized by atom transfer radical polymerization (ATRP). Different amounts of 1,3-propanesultone were used as quaternization agent to transit the PDMAEMA into partially modified poly(zwitterions), resulting in p[DMAEMA-co-3-dimethyl(methacryloyloxyethyl)ammonium propanesulfonate] (PDMAEMA-co-PDMAPS). Molecular weight, molecular weight distribution, and degree of quarternization were determined by gel permeation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…A decrease of intensity and an increase of R h is observed with increasing temperature. It is known that PDMAEMA is thermoresponsive in water solutions, having an LCST in the range 40–50 °C …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of intensity and an increase of R h is observed with increasing temperature. It is known that PDMAEMA is thermoresponsive in water solutions, having an LCST in the range 40–50 °C …”
Section: Resultsmentioning
confidence: 99%
“…When subjected to changes in pH and/or temperature it can switch from a hydrophilic to a less hydrophilic character. Also, PDMAEMA presents a lower critical solution temperature (LCST) in water in the range 40–50 °C, making it an attractive target for both physical studies and biomedical applications. In addition, due to its intrinsic cationic charge PDMAEMA has been proven to be an efficient gene‐transfer agent due to its ability in binding DNA by electrostatic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Thermoresponsive polymers showing lower critical solution or upper critical solution temperatures (LCST and UCST, respectively) in water as well as in electrolyte solutions are of great interest in a wide field of applications . In the last more than two decades, a lot of research efforts were devoted toward finding out new examples of polymers exhibiting LCST‐type transition, tuning of their critical temperatures, understanding the mechanism of phase transitions and applications .…”
Section: Methodsmentioning
confidence: 99%
“…Above the respective LCST, the polymer chains undergo a phase separation from the aqueous solution as a consequence of the rupture of the hydrogen bonds and increasing hydrophobic polymer–polymer interactions, showing a cloud point during turbidity measurements of polymer aqueous solutions. In this regard, poly[2‐(dimethylamino)ethyl methacrylate] p(DMAEMA) represents an interesting water soluble polymer that has been proposed for different biological applications and is one of the most investigated polymers whose aqueous solutions exhibit a cloud point behavior as a function of different properties such as molar mass, pH value, or comonomer composition . Despite many literature reports on this subject, and to the best of our knowledge, a systematic investigation is lacking describing the relationship of the cloud point of p(DMAEMA) with the molar mass in combination with a gradual change in its hydrophilic nature, i.e., by the quaternization degree of the tertiary amine present in its structure, still needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Armes and co‐workers demonstrated that a partial quaternization of a p(DMAEMA) homopolymer with a number average molar mass ( M n ) of 5300 g mol −1 , increased significantly the cloud points (1.0% w/v aqueous solutions at pH 8.8). More recently, Jung and Lee have reported that the cloud point of p(DMAEMA) ( M n = 15 700 g mol −1 ) can be adjusted at certain extent by quaternizing the polymer at different degrees by means of a rather demanding reaction with 1,3‐propane sulfone units. These latter investigations were based on the utilization of single p(DMAEMA)s with a predefined M n and, therefore, the effect of the molar mass on the cloud point was not addressed.…”
Section: Introductionmentioning
confidence: 99%